Türk ceza adalet sisteminde mağdur fail arabuluculuğu: Uzlaşma kurumunun yasal analizi - Tekin, Erim (İstanbul Bilgi Üniversitesi, 2010)
The aim of this study is to conduct a legal analysis of the practice of mediation that was introduced into the Turkish criminal justice system in the year of 2005 with new Criminal Law and Criminal Procedure Law. In this sense, alternative dispute resolution methods are examined to understand the concept of mediation beter. In addition to this, mediation is evaluated in relation to the principles of restorative justice. In this way, by examining the regulation and implementation of the mediation and reconciliation in Turkish criminal law, it is concluded that mediation model implemented in Turkey draws from model of victim-offender mediation models seen in other countries, which are based on restorative justice principle.

Bu çalışma ile amaçlanan, Türk ceza adalet sistemine 2005 yılında Ceza Kanunu ve Ceza Muhakemesi Kanunu ile giren uzlaşma kurumunun yasal analizinin yapılmasıdır. Bu anlamda uzlaşma kurumunun anlaşılabilmesi amacıyla, alternatif uyuşmazlık çözüm yolları değerlendirilmiştir. Bununla birlikte uzlaşma kurumu onarıcı adalet prensipleri ile birlikte değerlendirilmiş ve bu bakış açısıyla uzlaşma kurumunun, onarıcı adalet biçimlerinden biri olan mağdur-fail ara buluculuğu modelini yansıtıp yansıtmadığı hususu Türk hukukunda uzlaşmanın yasal düzenlenme ve uygulanma alanları değerlendirilmek suretiyle ortaya konulmaya çalışılmıştır.
Victim-offender mediation in Turkish criminal justice system: Legal analysis of the institution of reconciliation